2001
DOI: 10.1088/0022-3727/34/18/308
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polymer surfaces: atmospheric plasma versus vacuum plasma treatments

Abstract: An atmospheric pressure non-equilibrium plasma (APNEP) has been developed in the UK by EA Technology Ltd and is currently being investigated in collaboration with the University of Surrey. The main focus is the use of atmospheric pressure plasmas to modify the surfaces of commercially important polymers including polyolefins, poly(ethylene terephthalate) and poly(methyl methacrylate). These surface modifications include surface cleaning and degreasing, oxidation, reduction, grafting, cross-linking (carbonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(164 citation statements)
references
References 45 publications
6
146
0
7
Order By: Relevance
“…It was found that the roughness as measured using peak to valley (R p-v ), root mean squared (R q ) and average roughness (R a ) approximately doubles for the plasma treated APET samples. The roughened surface morphology is due to energetic species within the plasma impacting on the polymer surface [29][30][31]. …”
Section: Surface Morphology Of Plasma Treated Apetmentioning
confidence: 99%
“…It was found that the roughness as measured using peak to valley (R p-v ), root mean squared (R q ) and average roughness (R a ) approximately doubles for the plasma treated APET samples. The roughened surface morphology is due to energetic species within the plasma impacting on the polymer surface [29][30][31]. …”
Section: Surface Morphology Of Plasma Treated Apetmentioning
confidence: 99%
“…Surface modification of the CFs also alters their properties. Vacuum plasma treatment was adopted due to intriguing benefits such as effective surface modification, easy to operate, low cost and controlled treatment as compared to other surface modification techniques [20,21]. The surface modification and temperature dependent behaviour of waste cotton based CFs were studied by comparing the structural properties, wettability and response to nanoscale deformation.…”
Section: Introductionmentioning
confidence: 99%
“…), plasma enhanced chemical vapour deposition (PECVD) of thin films, plasma decontamination of toxic compounds, and recently in biomedical application and plasma medicine [1][2][3][4][5][6]. The dielectric barrier discharges (DBD) [1,2] and atmospheric pressure plasma jets (APPJ) [7] belong to the most successful designs.…”
Section: Introductionmentioning
confidence: 99%